Molecular Mechanisms in Amyotrophic Lateral Sclerosis: The Role of Angiogenin, a Secreted RNase - Aparicio-Erriu, Isabela M.; Prehn, Jochen (Frontiers in Neuroscience, 2012)
Amyotrophic lateral sclerosis is a fatal neurodegenerative disease caused by the loss of motoneurons. The precise molecular and cellular basis for neuronal death is not yet well established, but the contemporary view is that it is a culmination of multiple aberrant biological processes. Among the proposed mechanisms of motoneuron degeneration, alterations in the homeostasis of RNA binding proteins (RBP) and the consequent changes in RNA metabolism have received attention recently. The ribonuclease, angiogenin was one of the first RBPs associated with familial and sporadic ALS. It is enriched in motoneurons under physiological conditions, and is required for motoneuron survival under stress conditions. Furthermore, delivery of angiogenin protects cultured motoneurons against stress-induced injury, and significantly increases the survival of motoneurons in SODG93A mice. In this overview on the role of angiogenin in RNA metabolism and in the control of motoneuron survival, we discuss potential pathogenic mechanisms of angiogenin dysfunction relevant to ALS and other neurodegenerative disorders. We also discuss recent evidence demonstrating that angiogenin secreted from stressed motoneurons may alter RNA metabolism in astrocytes.